Psychological difficulties and challenges in the way of afghan students - Akbari, Sayed. Anwar.; Kamzanova, A. T. (ҚазҰУ Хабаршысы. Психология және әлеуметтану сериясы, 2017)
In this paper an attempt has been made to investigate Afghan students’ prob lems and offer mental health services. For this purpose, the study used the library research. Like Afghanistan in the past four decades involved of war, so the scientific work and research have faced more challenges. Therefore, in the field of children and students according psychopathology few research has been done. Despite be ing problems and challenges of students in the field of education and mental health service delivery, and identifying mental health, effective work has not been done. The study found that, more than six million eligible students do not have access to education, 300 schools are closed due to insecurity, only 60 percent of teachers are relative educated graduated fourteen grade or higher than, rate of teacher to students is from 32 up to 93, and 50 percent of schools are without building. So, in the past four years more than 2000 female students have been poisoned or mass hysteria. Whereas, the 48 percent of men and 75.8 percent of women are illiterate. In this study it also found that students with learning difficulties more traumatic ex periences 62 percent, 67.7 percent depression, and 72.2 percent had anxiety, also shown. Beyond, dispersed reports of suicide have also been given to the effect of failing to exam. According to mental health services, in all around the country there is only one hospital with 100 beds, 16 psychological counselling centers, countable and little psychiatrists. In addition, we found, that 20 percent of mentally ill clients refer to physician, whereas 80 percent of them are going to nonphysician. The purpose of this article is to review in general the educational situation of Afghan students; opportunities, possibilities, and challenges facing them. So continued to talk to psychological problems such as anxiety, depression, and trauma, which they are faced, and mental health services that are provided for them.